The Merits and Pitfalls of Participatory Action Research: Navigating Tokenism and Inclusion with Lived Experience Members - Tracy Smith-Carrier; Rana Van Tuyl (International Review of Public Policy)
This paper explores the merits and pitfalls of involving people with lived and living experiences of a phenomenon of interest (e.g., poverty, hunger, housing deprivation) in Participatory Action Research (PAR). As researchers who have conducted PAR and community-based research for several years, the authors have gained deep insight into the value of having lived/living experience members in PAR projects, as well as the challenges attendant to such work. Using a collaborative autoethnographic methodology, this paper provides an overview of PAR, including its purposes and objectives. Aiming to move past tokenistic inclusion, issues associated with meaningful participation, including relational (e.g., issues of power), ethical (e.g., risks of participation), emotional (e.g., research triggers), economic (e.g., remunerating contributions and financially supporting participation), representational (e.g., whose perspectives are advanced), and structural barriers (e.g., time, technological connectivity, etc.) are discussed using concrete examples. Bringing together people who may hold disparate perspectives, community ties, worldviews, and visions associated with a research undertaking can create challenges, but not including those who experience the phenomenon of study can create even more challenges.